Teatro sem arquitetura: as Brincadeiras do grupo Tá na Rua (1980-1983) - Galvão, Renata Silva de Oliveira (2012)
This work investigates the theatrical group "Tá na Rua" in the early formative years (1980 to 1983) in order to understand the development and consolidation of an identity which is called popular. With this analysis I try to unveil the group's political position in a debate that is inserted in the concepts of cultural resistance of the post-1964. For that, I'll stick to the script of the show "As Brincadeiras", which was built for street performances. With this research I tried to visualize and understand the historical process printed on the artistic composition of the group giving birth to the trajectories of actors who proposed "break" with the circuit of the rooms of the theater closed and "inaugurate" an alternative theater that dates back a popular culture in the relentless pursuit of approaching a target, and is recognized by the group as the "Brazilian people."